2002
DOI: 10.1902/jop.2002.73.10.1169
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Association Between Angiographically Defined Coronary Artery Disease and Periodontal Disease

Abstract: After accounting for factors common to both periodontal disease and CAD, there was no significant association between periodontal disease and chronic CAD as assessed angiographically. Further investigations into the relationship between periodontal disease and CAD should clearly separate chronic CAD and acute coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
2
27
2
4
Order By: Relevance
“…All these studies have shown a positive association between periodontal disease and CVD. This was also established in the studies by Ruquet et al .,[38] Geismar et al .,[39] Geerts et al .,[40] Malthaner et al .,[41] Geerts et al .,[40] Sim et al .,[42] Alman et al .,[43] Amoian et al .,[44] and Hashemipour et al . [45]…”
Section: Discussionsupporting
confidence: 56%
“…All these studies have shown a positive association between periodontal disease and CVD. This was also established in the studies by Ruquet et al .,[38] Geismar et al .,[39] Geerts et al .,[40] Malthaner et al .,[41] Geerts et al .,[40] Sim et al .,[42] Alman et al .,[43] Amoian et al .,[44] and Hashemipour et al . [45]…”
Section: Discussionsupporting
confidence: 56%
“…In the final statistical model, the odds ratio of 3.06 for the association between poor periodontal status and CHD remained statistically significant. Other studies have reported odds ratios of between 0.9 and 3.2 6‐9,11,12,26 for this association with evidence of a dose response between the severity of periodontitis and the occurrence of cardiovascular disease. A recent study in Sweden reported a much stronger association between acute myocardial infarction and chronic periodontitis with odds ratios ranging from 9.2 to 14.1 depending on the criteria used to identify periodontitis 10 .…”
Section: Discussionmentioning
confidence: 82%
“…However, they did not report any adjustment of confounding factors. Malthaner et al (2002) examined the relation between periodontal disease and asymptomatic coronary heart disease (CAD) where there was 50% stenosis in at least one of the epicardial arteries. Those without periodontal disease had less than 50% stenosis in these arteries.…”
Section: (Iv) Oral Health and Biomarkers Of Cardiovascular Diseasementioning
confidence: 99%